Concomitant use of dextromethorphan and alcohol‐induced dissociation in a patient with alcohol dependence - Yasuhito Nagai; Yuko Tajima; Koichi Miyakawa (PCN Reports)
Abstract Background Dextromethorphan (DXM) is an over‐the‐counter drug that is commonly abused by teenagers. Its main pharmacological property is a low‐affinity N‐methyl‐d‐aspartate (NMDA) receptor antagonist. Case Presentation We report acute psychotic dissociation induced by DXM and alcohol in a patient with alcohol dependence, which made it difficult to distinguish alcohol withdrawal symptoms with limited information. The psychotic symptoms were ameliorated by haloperidol; however, in cases of DXM abuse, haloperidol treatment should be avoided. Conclusion In the consultation of patients with addiction, the possibility of various addictive drugs must be kept in mind. The concomitant use of DXM and alcohol causes easy dissociation and high‐dose usage of DXM and alcohol withdrawal symptoms are difficult to distinguish.